Wardensmy Sport / Aniq Irfan Haqeem Romelan ... [et al.] - Romelan, Aniq Irfan Haqeem; Abdul Halim, Nabilah Syamimi; Mazli, Nurin Zahin; Abdul Latif, Nur Asilah Awatif; Ahmad, Inayatul Nur (2021)
Wardensmy Sport is the online business that offers high quality of sports equipment with affordable price. The services that they provide at their shop are printing service and free shipping foe the items that their customers had order from their shop. This company was founded by Muhammad Izzad Bin Mohd Noor Kamil in July 2019. At first, he starts the business since he was in secondary school without realizing that he actually already starting a business. Actually, that time he was 13 years old. He setup a full set jersey for his sports team. He also made his first profit about rm2++. Then when he starts entered Diploma, he had been asked by his lecturer to form a business for his subject called Entrepreneurship. So, his business journey was officially started when he entered his diploma study. Wardensmy promote their products by using social media such as Facebook and Instagram as their main platform. They also have their own website for their customers that doesn’t have social media. This is because their target audience is teenagers and adults. Most of the teenagers and adults nowadays have an account for each of the social medias and it will ease them to promote their products and gain more customers. The owner of Wardensmy Sport started or gain idea to run a business when he scrolling the Instagram. At the moment, he saw that many people are using Anti-slip Socks while exercise. So, he found out what is Anti-slip Socks. Then, he started to find out supplier for his company. He started his business with Rm0. How can He start his business with no money? Then he started to use pre-order system because he will not have to worried with any losses because customer will pay first to book for a product. So, he takes an order that reached 100 pairs of socks. He started with using mobile phone to promote his product to the social media. Day by day, his business starting to grow because the demand he gets was really good. Thus, it totally cost Rm0 for whoever want to start a business not necessary need money for RM5k to start a business. What actually they need is action not the fund. Without any action we can’t get anything but with an action we can earn a lot of money. Nowadays, each business will face a lot of challenges and problems. There are several problems that Wardensmy Sport faced to retain their customers. As for example, there are many competitors that sells the same products as Wardensmy Sport with cheaper price. The company had to improve their business in order to compete with other competitors.